Perceived and geographic food access and food security status among households with children. Issue 15 (2nd May 2016) - Ma, Xiaoguang; Liese, Angela D; Bell, Bethany A; Martini, Lauren; Hibbert, James; Draper, Carrie; Burke, Michael P; Jones, Sonya J
Abstract: Objective: To examine the association of both perceived and geographic neighbourhood food access with food security status among households with children. Design: This was a cross-sectional study in which participants' perceptions of neighbourhood food access were assessed by a standard survey instrument, and geographic food access was evaluated by distance to the nearest supermarket. Multinomial logistic regression models were used to examine the associations. Subjects: The Midlands Family Study included 544 households with children in eight counties in South Carolina, USA. Food security status among participants was classified into three categories: food secure (FS), food insecure (FI) and very low food security among children (VLFS-C). Results: Compared with FS households, VLFS-C households had lower odds of reporting easy access to adequate food shopping. VLFS-C households also had lower odds of reporting neighbourhood access to affordable fruits and vegetables compared with FS households and reported worse selection of fruits and vegetables, quality of fruits and vegetables, and selection of low-fat products. FI households had lower odds of reporting fewer opportunities to purchase fast food. None of the geographic access measures was significantly associated with food security status. Conclusions: Caregivers with children who experienced hunger perceived that they had less access to healthy affordable food in their community, even though grocery stores were present. Approaches to improve perceived access to healthy affordable food should be considered as part of the overall approach to improving food security and eliminating child hunger.